A case report on loss of vision secondary to odontogenic orbital cellulitis - Aria Amir Ghasemi; Huw Jones (Elsevier, 2021)
We report a rare case of complete loss of vision secondary to odontogenic orbital cellulitis. A 54 years old female presented with 3 days history of left sided periorbital swelling and nasal discharge complaining of increasing facial pain. She was diagnosed with orbital cellulitis and treated empirically with intravenous antibiotic. Despite initial medical treatment, symptoms worsened leading to loss of vision. Indirect fundoscopy confirmed a left central retinal artery occlusion. An urgent CT revealed left maxillary sinus opacification with diffuse periorbital oedema, proptosis and no drainable orbital collection. She underwent Lynch Howarth procedure to reduce the orbital pressure. Ischaemic optic neuropathy and central retinal artery occlusion secondary to tension orbit odontogenic orbital cellulitis with no orbital collection are rare. We propose by serial intraocular measurements and maintaining the pressure below 21 mmHg with topical and systemic treatments, the risk of visual loss in patients presenting with similar pathology can be reduced.